Obinutuzumab as consolidation after chemo‐immunotherapy: Results of the UK National Cancer Research Institute phase II/III GALACTIC trial. (26th August 2022) - Munir, Talha; Emmerson, Jake; Hockaday, Anna; Oughton, Jamie B.; Howard, Dena; Phillips, David; Neilson, Jeff; Pemberton, Nicholas; Paneesha, Shankara; Kennedy, Ben; Rawstron, Andy; Hillmen, Peter
Summary: The GA101 (obinutuzumab) monocLonal Antibody as Consolidation Therapy In chronic lymphocytic leukaemia (CLL) (GALACTIC) was a seamless phase II/III trial designed to test whether consolidation with obinutuzumab is safe and eradicates minimal residual disease (MRD) and, subsequently, whether this leads to prolonged progression‐free survival (PFS) in patients with CLL who have recently responded to chemo‐immunotherapy. Patients with a response 3–24 months after chemotherapy were assessed for MRD. MRD‐positive patients were randomised to receive consolidation therapy with obinutuzumab or no consolidation. The trial closed after the phase II part due to slow recruitment. In all, 48 patients enrolled of whom 19 were MRD negative and were monitored. Of the 29 MRD‐positive patients, 14 were randomised to receive consolidation and 15 to no consolidation. At 6 months after randomisation, 10 and 13 consolidated patients achieved MRD negativity by flow cytometry (sensitivity 10 −4 ) in bone marrow and peripheral blood respectively. PFS was significantly better in consolidated patients compared to non‐consolidated patients ( p = 0.001). No difference was observed in PFS, overall survival or duration of MRD negativity when comparing the 10 MRD‐negative patients after consolidation with the 19 MRD‐negative patients in the monitoring group. Common adverse events in the consolidation arm were thrombocytopenia, infection, and cough. Only 1% of events were infusion‐related reactions. This observation provides further evidence that consolidation to achieve MRD negativity improves outcomes in CLL and that obinutuzumab is well tolerated in patients with low levels of disease.